Where Is It Like to Be an Octopus? - Carls-Diamante, Sidney (Frontiers in Systems Neuroscience, 2022)
The cognitive capacities and behavioural repertoire of octopuses have led to speculation that these animals may possess consciousness. However, the nervous system of octopuses is radically different from those typically associated with conscious experience: rather than being centralized and profoundly integrated, the octopus nervous system is distributed into components with considerable functional autonomy from each other. Of particular note is the arm nervous system: when severed, octopus arms still exhibit behaviours that are nearly identical to those exhibited when the animal is intact. Given these factors, there is reason to speculate that if octopuses do possess consciousness, it may be of a form highly dissimilar to familiar models. In particular, it may be that the octopus arm is capable of supporting an idiosyncratic field of consciousness. As such, in addition to the likelihood that there is something it is like to be an octopus, there may also be something it is like to be an octopus arm. This paper explores this possibility.